Nonmelanoma Facial Skin Cancer: A Review of Diagnostic Strategies, Surgical Treatment, and Reconstructive Techniques. Issue 12 (July 2019) - Badash, Ido; Shauly, Orr; Lui, Christopher G; Gould, Daniel J; Patel, Ketan M
Nonmelanoma skin cancer is the most common form of cancer in the United States, and the face is a common area for skin cancer development due to its frequent exposure to the sun. This article focuses on the surgical management of facial nonmelanoma skin cancers, including diagnostic considerations, biopsy techniques, and staging. In addition, we discuss surgical treatment options, including indications, techniques, outcomes, and facial reconstruction following tumor excision.